Study on the Limitation of Liability for Ship Oil Pollution Removal Costs: Comment on "The First Accident of Condensate Leakage from a Tanker Carrying Condensate into the Sea" - Liu, Jiayi (International Journal of Social Sciences and Public Administration, 2025)
Compensation for ship pollution cleanup costs belongs to civil liability, and there is a possibility of limiting liability for the non-persistent cargo oil carried by the vessel SANCHI. Currently, there are problems such as limitation of oil type, subject dispute, non-uniformity of compensation scope and rate standard, and low liability limit in the case of compensation for damage caused by ship pollution in China, etc. The system of limitation of liability in the Maritime Law should be further improved by authorizing the clean-up unit to claim compensation on its own, the subject of responsibility for the ship’s clean-up fee should be jointly and severally liable, clarifying the scope and standard of the clean-up fee, and moderately increasing the limit of compensation.